2022
DOI: 10.3389/fpsyg.2022.748704
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Official Corruption, Satisfaction With Government Performance, and Subjective Wellbeing—An Empirical Study From China

Abstract: Both corruption and subjective wellbeing are of concern to academics and governments. Although some evidence suggests that corruption deteriorates subjective wellbeing, the relationship between perception of official corruption and subjective wellbeing is still unknown. This study aims to examine the link between perceived official corruption and subjective wellbeing in the context of China and whether satisfaction with government performance has a mediating effect in the process. Based on data from China Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
0
8
0
2
Order By: Relevance
“…In particular, we would like to underline the importance of internal auditing in public organizations as a way to detect and reduce corruption. Corruption severely undermines the development process, as it is negatively related to fiscal space (Katuka and Mudzingiri 2023), productivity (Borovic and Radicic 2023), and subjective well-being (Ma et al 2022). Jeppesen (2019) argues that "commercial and political corruption leads to misstatements in the financial statements of both the corruption giver's and the corruption receiver's organizations".…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, we would like to underline the importance of internal auditing in public organizations as a way to detect and reduce corruption. Corruption severely undermines the development process, as it is negatively related to fiscal space (Katuka and Mudzingiri 2023), productivity (Borovic and Radicic 2023), and subjective well-being (Ma et al 2022). Jeppesen (2019) argues that "commercial and political corruption leads to misstatements in the financial statements of both the corruption giver's and the corruption receiver's organizations".…”
Section: Literature Reviewmentioning
confidence: 99%
“…A lack of anti-corruption awareness encourages young people to tolerate bribes. Rose-Ackerman and Palifka (2016) observed correlations between quality of life and the propensity for corruption, while Ma et al (2022) found that the more satisfied a person is with their living conditions, the less likely they are to think about offering a bribe. Although one might state that quality of life and financial insecurity are correlated (Karam et al, 2022), the perceived quality of life has many more dimensions than just financial (Felce and Perry, 1995;Haraldstad et al, 2019;Costa et al, 2021), most of which are of a subjective nature and cannot be assessed by hard data and metrics (Ridzi et al, 2020).…”
Section: Hypotheses Buildingmentioning
confidence: 99%
“…According to Ma et al [23], perceptions of official corruption are negatively related to subjective well-being. Corruption tends to lower income and it is one of the most important generators of poverty [24].…”
Section: Impact Of the Perception Of Corruption On Happinessmentioning
confidence: 99%
“…Experiences of corruption have detrimental effects on individuals' mental health. Thus, corruption can undermine citizens' happiness, but governments can remedy those negative impacts by improving government performance [23].…”
Section: Impact Of the Perception Of Corruption On Happinessmentioning
confidence: 99%